Реконструкція 3D моделей будівель за їх тінями за допомогою супутникових знімків - Habraman, H.; Mozhovoy, D. K. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2020)
The creation of three-dimensional models of buildings using aerospace images in recent years has become a very relevant and sought-after area, since such models are now used in various fields of human activity. Currently, the creation of such models can be performed in various ways: using stereo shooting from a satellite, taking pictures from a quadcopter, measuring by an airplane lidar by scanning a building from the Earth. But all these methods require expensive equipment and highly qualified professionals, which is a limiting factor for the widespread use of these technologies by ordinary users. The purpose of this article was to show an alternative solution for creating three-dimensional models of buildings based on satellite imagery and free software. In this work, we used the well-known software packages – Google Earth and SketchUp.